Tracking endothelium-dependent NO release in pressurized arteries - Wallis, Lillian; Donovan, Lucy; Johnston, Aaron; Phillips, Lauren C.; Lin, Jinheng; Garland, Christopher J.; Dora, Kim A. (Frontiers in Physiology, 2023)
Background: Endothelial cell (EC) dysfunction is an early hallmark of cardiovascular disease associated with the reduced bioavailability of nitric oxide (NO) resulting in over-constriction of arteries. Despite the clear need to assess NO availability, current techniques do not reliably allow this in intact arteries. Methods: Confocal fluorescence microscopy was used to compare two NO-sensitive fluorescent dyes (NO-dyes), Cu2FL2E and DAR-4M AM, in both cell-free chambers and isolated, intact arteries. Intact rat mesenteric arteries were studied using pressure myography or en face imaging to visualize vascular smooth muscle cells (SMCs) and endothelial cells (ECs) under physiological conditions. Both NO-dyes irreversibly bind NO, so the time course of accumulated fluorescence during basal, EC-agonist (ACh, 1 µM), and NO donor (SNAP, 10 µM) responses were assessed and compared in all experimental conditions. To avoid motion artefact, we introduced the additional step of labelling the arterial elastin with AF-633 hydrazide (AF) and calculated the fluorescence ratio (FR) of NO-dye/elastin over time to provide data as FR/FR0. Results: In cell-free chambers using either Cu2FL2E or DAR-4M AM the addition of SNAP caused a time-dependent and significant increase in fluorescence compared to baseline. Next, using pressure myography we demonstrate that both Cu2FL2E and DAR-4M AM could be loaded into arterial cells, but found each also labelled the elastin. However, despite the use of different approaches and the clear observation of NO-dye in SMCs or ECs, we were unable to measure increases in fluorescence in response to either ACh or SNAP when cells were loaded with Cu2FL2E. We then turned our attention to DAR-4M AM and observed increases in FR/FR0 following stimulation with either ACh or SNAP. The addition of each agent evoked an accumulating, time-dependent and statistically significant increase in fluorescence within 30 min compared to time controls. These experiments were repeated in the presence of L-NAME, an NO synthase inhibitor, which blocked the increase in fluorescence on addition of ACh but not to SNAP. Conclusions: These data advance our understanding of vascular function and in the future will potentially allow us to establish whether ECs continuously release NO, even under basal conditions.